The Role of Inspectorate Audit on the Quality of Budget Realization Reports with Expertise as a Moderating Variable - Ronal Korano; Ismail R. Noy; Edwin Lamat Abraham Karundeng; Tarsono; Rumidi (Faculty of Business and Economics , Universitas Yapis Papua, 2023)
Budget realization reports produced by work units within the Regional Government are largely determined by the role of the Government's Internal Supervisor. The role of Government Internal Supervisors will be more optimal if supported by the expertise they have in supporting the quality of reports that are relevant, reliable, comparable, and understandable. This research aims to analyze the influence of the Inspectorate's audit role on the quality of budget realization reports with expertise as a moderator variable. This type of research is explanatory quantitative using survey methods. The survey was conducted using a non-probability sampling design with a purposive sampling technique of 38 Papua Province Inspectorate employees. The results of research using the Structural Equation Model Partial Least Square (SEM-PLS) analysis method found that Inspectorate audits had a positive impact on budget realization reports, while expertise as a moderator variable was also able to moderate the relationship between Inspectorate audits and budget realization reports.